Peer support among student teachers through close social bonds - Knut-Andreas Abben Christophersen; Eyvind Elstad; Corinna Geppert; Astrid Schmidt; Are Turmo (Освітній вимір, 2025)
This study explores the impact of peer support on 471 student teachers during the practicum phase, particularly how such support can influence their motivation and self-efficacy. Questionnaires were distributed to student teachers in Schleswig-Holstein, Germany, with all measures based on established scales. The survey was validated for internal consistency, resulting in a high response rate. Data were analysed using structural equation modelling, demonstrating an acceptable fit for the proposed model. The results indicate that motivation to become a teacher is the strongest predictor of peer support; altruistic motivation has a weaker correlation. Additionally, teacher self-efficacy during various practicum phases is positively associated with peer support, whereas perceived disciplinary issues in the classroom negatively impact instructional self-efficacy. These findings highlight the need for structured peer support systems in teacher education to enhance student teachers' experiences and for further research into the dynamics of peer relationships in educational settings.